6(x-3)+10=2(4x-3)

Simple and best practice solution for 6(x-3)+10=2(4x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-3)+10=2(4x-3) equation:



6(x-3)+10=2(4x-3)
We move all terms to the left:
6(x-3)+10-(2(4x-3))=0
We multiply parentheses
6x-(2(4x-3))-18+10=0
We calculate terms in parentheses: -(2(4x-3)), so:
2(4x-3)
We multiply parentheses
8x-6
Back to the equation:
-(8x-6)
We add all the numbers together, and all the variables
6x-(8x-6)-8=0
We get rid of parentheses
6x-8x+6-8=0
We add all the numbers together, and all the variables
-2x-2=0
We move all terms containing x to the left, all other terms to the right
-2x=2
x=2/-2
x=-1

See similar equations:

| 8c=144 | | -7=x^2-8x | | 11a+14=36 | | x+120=254 | | 25x+250=1000 | | y-(-4)=19 | | t/(-10)=60 | | 8w=20.8. | | 2y−7=19 | | 32.91=-7.35-6.1m | | d+17=-6 | | 12v+10v+14=80$ | | -5-8x+25=4 | | X-12=2x-12=2 | | 8p+25=57 | | 40-6x=2x | | 8x*4=40 | | 3x-1=-x+5+4 | | 11g+12=56 | | 3x+7=+19 | | 29.12=-1.6(n-9.4) | | x/6=-42 | | -8x=7.6 | | 15c+7=37 | | -2(x+12)=20 | | 7(x+2)+5x=3+2(x-4) | | 2/3(9x–15)=14 | | –3(j−84)=15 | | 3c=123c=12 | | (y+1)²=9 | | 8(k+3)=60 | | -3(x-17)=9 |

Equations solver categories